2012
DOI: 10.1371/journal.pone.0048907
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Sound Emission of Elephant Vocalizations: Evidence for Two Rumble Production Types

Abstract: Recent comparative data reveal that formant frequencies are cues to body size in animals, due to a close relationship between formant frequency spacing, vocal tract length and overall body size. Accordingly, intriguing morphological adaptations to elongate the vocal tract in order to lower formants occur in several species, with the size exaggeration hypothesis being proposed to justify most of these observations. While the elephant trunk is strongly implicated to account for the low formants of elephant rumbl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 50 publications
3
65
0
Order By: Relevance
“…Whether the adductory manoeuvres performed in this study exactly resemble those of in vivo vocalization would need to be established in future studies, which will be very challenging to perform as direct endoscopic evaluation of vocal fold vibration in a live animal is virtually impossible with the current technological means. However, several arguments speak in favour of a faithful duplication of natural vocalization conditions: (1) the laryngeal configuration was created in the only way possible to easily induce phonation in our excised larynx; (2) similar adductory gestures to the ones we used in the excised larynx experiments have been documented in humans; and (3) the acoustic output of the excised larynx was closely comparable to sounds captured from in vivo vocalizations, with fundamental frequencies that were well within the range of those reported for the 'rumble' call type (Poole et al, 1988;Langbauer, 2000;Herbst et al, 2012;Stoeger et al, 2012). The mammalian larynx is a non-linear system capable of exhibiting a wide range of vibratory behaviour, such as periodic vibration, subharmonics and deterministic chaos (Titze et al, 1993a;Herzel et al, 1995;Behrman and Baken, 1997;Fitch et al, 2002;Neubauer et al, 2004;Jiang et al, 2006).…”
Section: Physiological Relevancementioning
confidence: 81%
“…Whether the adductory manoeuvres performed in this study exactly resemble those of in vivo vocalization would need to be established in future studies, which will be very challenging to perform as direct endoscopic evaluation of vocal fold vibration in a live animal is virtually impossible with the current technological means. However, several arguments speak in favour of a faithful duplication of natural vocalization conditions: (1) the laryngeal configuration was created in the only way possible to easily induce phonation in our excised larynx; (2) similar adductory gestures to the ones we used in the excised larynx experiments have been documented in humans; and (3) the acoustic output of the excised larynx was closely comparable to sounds captured from in vivo vocalizations, with fundamental frequencies that were well within the range of those reported for the 'rumble' call type (Poole et al, 1988;Langbauer, 2000;Herbst et al, 2012;Stoeger et al, 2012). The mammalian larynx is a non-linear system capable of exhibiting a wide range of vibratory behaviour, such as periodic vibration, subharmonics and deterministic chaos (Titze et al, 1993a;Herzel et al, 1995;Behrman and Baken, 1997;Fitch et al, 2002;Neubauer et al, 2004;Jiang et al, 2006).…”
Section: Physiological Relevancementioning
confidence: 81%
“…The exact mechanism for the production of infrasound in elephants is currently unknown, but is presumed to involve the larynx and trunk (Herbst et al, 2012; Stoeger et al, 2012). It is thus possible that the enlarged cerebellum is related to vocalization; however, we have found that, in contrast to the elephant, the relatively large cerebellum of echolocating microchiropterans is not an enlarged cerebellum, but rather the result of a diminished cerebral cortex, possibly related to miniaturization (Herculano-Houzel et al, in preparation).…”
Section: Resultsmentioning
confidence: 99%
“…[1][3]). It has been hypothesised that rhinos might be using infrasound for long-distance communication which would be similar to the communication of elephants [4], [5].…”
Section: Introductionmentioning
confidence: 99%